1998
DOI: 10.1007/s004170050079
|View full text |Cite
|
Sign up to set email alerts
|

Retinal sensitivity measurement over drusen using scanning laser ophthalmoscope microperimetry

Abstract: Large drusen may influence retinal sensitivity and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 11 publications
0
14
0
2
Order By: Relevance
“…[8][9][10][11] In contrast, other studies reported no difference in sensitivity between drusen and nondrusen areas.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…[8][9][10][11] In contrast, other studies reported no difference in sensitivity between drusen and nondrusen areas.…”
Section: Resultsmentioning
confidence: 88%
“…[3][4][5][6][7] Functional loss due to AMD was previously demonstrated by findings of reduced visual field sensitivity in retinal locations with drusen compared with nondrusen locations, using scanning laser ophthalmoscope (SLO) perimetry and microperimetry. [8][9][10][11] In contrast, other studies reported no difference in sensitivity between drusen and nondrusen areas. 12 Optical coherence tomography (OCT) is a noninvasive imaging technique that provides cross-sectional images of retinal layer structure, useful for visualization of pathology.…”
Section: Resultsmentioning
confidence: 88%
“…Entretanto, a sensibilidade macular parece ser a mesma em áreas com e sem drusas (17) . Não foi observada diferença de sensibilidade sobre drusas moles, entretanto encontrou-se diferença de sensibilidade retiniana na área de drusas grandes utilizando o ORL (21) . Tais autores definiram drusas moles como aquelas com margens mal definidas e drusas grandes como aquelas com margens bem definidas, ambas acima de 125 µm.…”
Section: Discussionunclassified
“…Esses autores provavelmente utilizaram áreas de atrofia nesse grupo de drusas grandes, pelas características anatômicas descritas e pelo resultado de escotomas absolutos (zero dB), encontrados em algumas áreas, demostrando atrofia retiniana nesse local. Estas importantes diferenças na metodologia e na interpretação dos resultados utilizados por outros autores (21) podem justificar a diferença de seus resultados em relação aos encontrados neste estudo. Há também relatos de diminuição da sensibilidade em olhos com drusas, porém esse grupo, reconhecendo a limitação do método de perimetria utilizado (Humphrey 10-2), não sugeriu a correlação direta das drusas com a diminuição de sensibilidade, preferindo atribuir tal diminuição a um processo difuso que acomete EPR e retina sensorial.…”
Section: Discussionunclassified
“…No change was noted over areas of soft drusen, nor was any correlation found between drusen size and severity of sensitivity loss. 109 Vujosevic and colleagues used this device to demonstrate a decrease in retinal sensitivity in patients with increased FAF signal in the junctional zone surrounding GA. 110 This suggested that LF accumulation in RPE cells surrounding areas of GA resulted in a functional deficit. 71 This supports a previously mentioned observation that the accumulation of LF in the junctional zone precedes the expansion of GA. 65 With the introduction of the MP-1 (Nidek Technologies, Gamagori, Japan), MP was automated and designed to test identical points on the retina during baseline and follow-up testing.…”
Section: Microperimetrymentioning
confidence: 99%